Standardization in the judgment of line orientation test in elderly people in Northeast Brazil - Paulo Roberto de Brito-Marques; Janaina Mariana de Araujo Miranda Brito-Marques; Cácia Carolina de Carvalho Silva Miranda; Herickssen Gustavo Medeiros-Silva (Dementia & Neuropsychologia)
ABSTRACT. Aging is generally associated with a decline in cognition when compared to adulthood. The changes most seen are in attention, perception, working memory, short-term memory, free recall, and processing speed. Certain changes in the Judgment of Line Orientation (JLO) test may be present in elderly people. Objective: The objective of this study was to describe the difference among age, sex, schooling, Mini-Mental State (MMS), and Mini-Mental State Examination (MMSE) when compared to the JLO test in elderly people. The second is to assess the clinical use of the JLO test in elderly people's cognitive decline in Northeast Brazil. Methods: A cross-sectional, randomized study was carried out on 280 elderly people, between 60 and 89 years old, and the mean age was 69.4 (±6.8 years SD); 73.9% of the females lived in Olinda City, State of Pernambuco, Brazil. Age was stratified every 5 years between 60 and 89 years old, and schooling was divided into four subgroups between illiterate and more than 8 years of schooling. Each participant was submitted to an analysis of age, sex, schooling, risk factors, MMS, modified MMSE, and a JLO test. Results: There was no statistical difference between the sexes. However, there was a statistical difference when compared to the JLO test and age (p<0.012), schooling (p<0.001), MMS (p<0.001), and modified MMSE (p<0.001). Conclusion: We observed that with a cutoff point of 18 points, the JLO test is indicated to assess visuospatial and visuoperceptive changes in elderly people in Northeast Brazil.